Perbedaan Kejadian Diare Akut Antara Anak Riwayat Pemberian Asi Eksklusif Dengan Anak Riwayat Pemberian Pasi Pada Usia 7-24 Bulan - Hapilah, Yessi Nur, Prof. Dr. Bambang Soebagyo, dr., Sp.A (K) (2017)
Background: Diarrhea is one of the causes of death in developing countries. The supporting factors that increase the risk of diarrhea are like unclean environment, malnutrition, measles, immunodeficiency, not washing-hand habit, and children who do not get exclusive breast milk. Exclusive breast milk has many benefit for children to prevent infectious diseases because breast milk has protective substances or immune substance especially sIgA. Objective: This Research aims to know the difference of acute diarrhea between children who receive breast milk and children who receive alternate breast milk at 7 until 24 months old. Methods: This Research use observational analytic methods with cross sectional research design and also use purposive sampling technique in some of Posyandu in the working area of Puskesmas Gatak, Sukoharjo Regency, with 55 children as samples. Results: Among 55 samples, it founds that children who receive exclusive breast milk and get acute diarrhea are 3 children (12.5%), while the children who receive alternate breast milk and get acute diarrhea are 21 children (87.5%). As for children who receive exclusive breast milk and do not get acute diarrhea are 22 children (71.0%), while the children who receive alternate breast milk and do not get acute diarrhea are 9 children (29%). Statistical test result with Chy Square test gets P value=0,000, P < 0,05 which that means the are some meaningful difference. Conclusions: The acute diarrhea cases with children who receive exclusive breast milk are less than the children who receive alternate breast milk